Diversity and Seasonal Fluctuations of Arthropod Fauna in Bangladesh Deepwater Rice (Bangladesh Rice Journal, 2014)
An intensive study of the diversity of arthropod fauna in Bangladesh deepwater rice ecosystem from 1977 to 1980 revealed: 139 phytophages, 75 predators, 75 parasitoids and 44 scavengers identified to species level. Adding those forms identified to family/subfamily brought the total to 375 species. Insecta comprised 354 species belonging to more than 100 families. This is a conservative estimate since the main sampling methods used, sweepnetting and the rearing of parasitoids, is fairly effective for mid- and upper canopy forms, but is not effective for collecting fauna in the benthos, neuston and lower plant canopy for which a suction sampler is necessary.There was a marked seasonal fluctuation in numbers and composition of the fauna due mainly to the nature of the deepwater rice plant and the annual flooding pattern. The preflood period was conducive to moderate buildups of some canopy-living insects. In the flooding period the numbers of many arthropods crashed precipitously and never recovered (eg leafhoppers and planthoppers). Those forms adapted to deep flooding continued at moderate levels (eg acridids, green leafhopper), while a few arthropods were able to increase their numbers (eg tettigonids, yellow stem borer and spiders). Spiders, the most abundant predator group, were numerous at all times even during deep flooding and they probably limited the numbers of leafhoppers, planthoppers and some other pests. In addition, 75 parasitoids formed part of the faunal community and attacked many phytophages.DOI: http://dx.doi.org/10.3329/brj.v17i1-2.20903Bangladesh Rice j. 2013, 17(1&2): 75-104